Smartphone intervention for pregnancy smoking cessation with peer support: the study protocol of the SmokeFree Together 2.0 (SFT 2.0) randomised controlled trial - Ken Resnicow; Kristie Foley; Daniel Muresan; Oana M Blaga; Marina D Dascal; Alexandra Onișor; Teodora Frățilă; Andreea Morar; Dan Mihu; Cristian I Iuhas; Gabriela Caracostea; Cristian I Meghea (BMJ Open)
Introduction Smoking in pregnancy negatively impacts the mother’s and offspring’s health. Mobile health, especially mobile phone-based approaches, shows promise in supporting pregnant women to quit smoking. Our previous research indicated that support from laypersons, such as family, friends and coworkers, can increase smoking cessation. Building on these findings, we developed an innovative smartphone application (app) that combines the power of social support with artificial intelligence. The app leverages the unique functionality of smartphones and reinforcement learning (RL) to provide a deeply tailored intervention that continuously adapts while emphasising positive support through reciprocal interactions between the smoker and the support person. Herein, we report the methods used to develop, implement and test the feasibility and effectiveness of a novel adaptive mobile pregnancy tobacco cessation app-based intervention using deep tailoring and a self-nominated supporter.Methods and analysis The study is a type II hybrid effectiveness-implementation randomised controlled trial. In total, 300 pregnant smokers and their supporters will be randomised to (1) the SmokeFree Together 2.0 app and an RL-based intervention that continuously decides if a counselling call is needed using a fixed algorithm measuring motivation and craving or (2) a control group. The intervention will be administered throughout pregnancy up to 1 month after giving birth, with a 5-month follow-up period and outcome assessments at 3-month and 6-month post partum. Cessation (primary outcome) is defined as 7-day point biochemically verified prevalence of tobacco use and abstinence since birth, assessed at 6 months post partum. The central hypothesis is that the intervention will show evidence of feasibility and effectiveness in increasing social support, pregnancy cessation and postnatal abstinence.Ethics and dissemination The Institutional Review Board of Michigan State University (#IRB00000297) approved this trial. The findings will be disseminated through peer-reviewed publications and participation in scientific conferences.Trial registration number NCT05337722. Protocol version: 1.3 from 15.05.2024.